A case study of maintenance of fire prevention - Mohd Azizi, Alias (2017)
One of the main objectives in the design of the building is to provide a structure that can meet the tastes of the owner and in accordance with the purpose of the building was developed. The building is designed well and will be able to use the space efficiently and has the aesthetic and attractive environment. In designing the building, security features, and then makes the maintenance of fire fighting equipment and fire prevention system should be considered accordingly. Most of the buildings built with a sophisticated design and has the tools and a good fire prevention system and modern technology, modern high. Unfortunately, the tools and the system is idle and low note about maintenance, resulting in the occurrence of fire equipment and systems were not functioning causing a fire easily. Considering the fact that the building was built for a specific use or activity, the safety of life due to fire should be given due consideration when designing the building. Maintenance must comprise from the outset when the building was originally designed. Appropriate measures need to be taken into account so that the occupants of the building on the top floor have the same or less risk than residents of buildings that are ranked above the ground. This can be done by performing security measures such as the maintenance of active and passive devices and fire suppression system partition as well as building and designing roads out good safety and appropriate to the occupants of the building.